2009
DOI: 10.1007/s00125-009-1297-8
|View full text |Cite
|
Sign up to set email alerts
|

A common variant in MTNR1B, encoding melatonin receptor 1B, is associated with type 2 diabetes and fasting plasma glucose in Han Chinese individuals

Abstract: Aims/hypothesis Recently, three groups independently reported that variation in MTNR1B, the gene encoding melatonin receptor 1B, was associated with an increased risk of type 2 diabetes, increased fasting plasma glucose and impaired insulin secretion in populations of European ancestry. In the present study, we investigated whether a single MTNR1B polymorphism was associated with type 2 diabetes in Han Chinese individuals, to elucidate whether this is a cross-populational effect. Methods The MTNR1B variant rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
78
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 11 publications
15
78
0
Order By: Relevance
“…All recently published articles on the variation in MTNR1B report an association with elevated fasting plasma glucose [56,[64][65][66]. This appears to be accounted for by impaired beta cell function; we demonstrated that this is reduced in the early phase of insulin secretion [56], while another report indicated impaired beta cell function as assessed by HOMA (HOMA-B) [65].…”
Section: Genome-wide Association Studies and Mtnr1bmentioning
confidence: 45%
See 1 more Smart Citation
“…All recently published articles on the variation in MTNR1B report an association with elevated fasting plasma glucose [56,[64][65][66]. This appears to be accounted for by impaired beta cell function; we demonstrated that this is reduced in the early phase of insulin secretion [56], while another report indicated impaired beta cell function as assessed by HOMA (HOMA-B) [65].…”
Section: Genome-wide Association Studies and Mtnr1bmentioning
confidence: 45%
“…Thus, it is likely that the SNPs reported to be associated with MTNR1B tag the same signal. Very recently, associations of rs10830963 with elevated fasting plasma glucose and future risk of type 2 diabetes was confirmed in a Chinese population [66].…”
Section: Genome-wide Association Studies and Mtnr1bmentioning
confidence: 90%
“…While some studies have shown reproducible associations [9,11,12,19,20], it remains to be further defined to what degree loci discovered in Europeans will show an association in populations of different ancestries. In addition, to localise the variant(s) responsible for an association signal, we need to generate a comprehensive list of potential causal variants in the regions of interest, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that genetic effects explain 54.8% of the variance of glucose levels in a European population [4]. Recent progress in complex-trait genetics has allowed the identification of loci regulating FPG levels [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diabetes is coupled with lower melatonin levels as reduction in serum melatonin and higher insulin level is observed in type 2 diabetic Goto Kakizaki rats (6). Genome-wide association studies has shown that specific single-nucleotide polymorphisms of the melatonin receptor 2 (MTNR1B) locus is linked with an increased blood glucose concentration and type 2 diabetes (8)(9)(10)(11)(12)(13). Melatonin can be able to bring anti-hyperglycemic effect either by improving insulin sensitization or by improvement of insulin secretion, or both.…”
Section: Introductionmentioning
confidence: 99%